A choice of retirement age decision among government servant : A case study in Rh Kayak - Shirley Szebah, Anak Mambai (Universiti Malaysia Sarawak (UNIMAS), 2015)
Malaysian government facing demographic transformations as senior employees whom have a rich experience in working start retiring and this has become a major concerns.In the 1 sl October 2001, Malaysian government has increased the compulsory retirement age from 55 to 56 years. No longer after that, in 1 st July 2008, Malaysian government further increased the retirement age from 56 to 58 years old. The latest amendment regarding retirement age occurred again on the 1st January 2012. The government again increased the compulsory retirement age from 58 to 60 years old. Due to this, it is important for us to understand the ability, the wants and the needs of employees regarding retirement